If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -2 = 11x + 7 Reorder the terms: -2 + 8x = 11x + 7 Reorder the terms: -2 + 8x = 7 + 11x Solving -2 + 8x = 7 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -2 + 8x + -11x = 7 + 11x + -11x Combine like terms: 8x + -11x = -3x -2 + -3x = 7 + 11x + -11x Combine like terms: 11x + -11x = 0 -2 + -3x = 7 + 0 -2 + -3x = 7 Add '2' to each side of the equation. -2 + 2 + -3x = 7 + 2 Combine like terms: -2 + 2 = 0 0 + -3x = 7 + 2 -3x = 7 + 2 Combine like terms: 7 + 2 = 9 -3x = 9 Divide each side by '-3'. x = -3 Simplifying x = -3
| .5(5x+4)-.33(x+7)=4 | | 81+8=6+5 | | 3x+15=33 | | 8-81=5-6 | | 3(y-8)=4(2y+9) | | 2x=7+-43-8x | | 9-p=4p-11 | | 2x-10=7x-11 | | 6a-16+6a-15+6a+7=48 | | -4x+6+x=-2x+x-10 | | -3x-8+x=-4x+-10 | | c/4=16 | | x-(-12)=2 | | 2(x+10)-5(2-x)+3=0 | | 81-4x^2=0 | | x-(-8)=-28 | | (x^2-11+19-x)(-10)= | | (3x-5)+(3x+5)+x=180 | | 4m^3-9=23 | | x-(-1)=50 | | 3.2b+8=20 | | 2+6x-3-3x=0 | | 22=4(5y-2) | | x-(-5)=10 | | x+(x+5)+x+(x+5)=26 | | 19=17-2x | | 9-5t=3t+18 | | 5x+4=13x-68 | | 9x^2+16=24x | | 3p^2+5=32 | | 19x-7=1+17x | | Q=650-5P-P^2 |